PENGGUNAAN KAMERA THERMAL IMAGING UNTUK PENGECEKAN KEBOCORAN REFRIGERAN PADA SISTEM REFRIGERASI - Mitrakusuma, Windy Hermawan; Ramadhan Siswanto, Muhammad Raja Bara; Sekar Ayu, Wirenda (KURVATEK, 2022)
This paper analyzes the use of thermal imaging camera to check for refrigerant leak on a refrigeration system. In a RHVAC system maintenance procedure, one of the processes is checking for leaks in the RHVAC system pipe. There are various methods of conducting a leak check on the RHVAC system. In this research, a leak detection procedure will be carried out using a method that is rarely used, namely using a thermal imaging camera. This tool can capture an image of an object using infrared radiation so that the temperature distribution of the object can be seen in the photos produced by this thermal imaging camera. In a fluid leak such as refrigerant, there will be a throttling process which causes a difference in the temperature of the fluid in the pipe with the temperature of the fluid that comes out through the leak hole. With thermal imaging camera the results of the leak can be detected, but there are some limitations of the camera that need to be considered in the leak checking procedure so that the results obtained are optimal.